Full-depth Mediterranean nitrate δ15N and δ18O data and TN δ15N data - Tanja Wald; François Fripiat; Alan Foreman; Toste Tanhua; Guy Sisma-Ventura; Yeongjun Ryu; Dario Marconi; Daniel M Sigman; Gerald H Haug; Alfredo Martínez-García (PANGAEA, 2025)
Nitrate δ15N (vs. AIR) and δ18O (vs. VSMOW) measurements have been performed using the denitrifier method (Weigand et al., 2016) on seawater samples from the cruises MSM72 (2018), TalPro (2016) and HaiSec45 (2021). Samples with detectable amount of nitrite has been treated with sulfamic acid before isotope analysis (Granger and Sigman, 2009). This dataset provides full-depth nitrate-only δ15N and δ18O profiles across the Mediterranean Sea which shows a basin-wide 15N depletion relative to the global ocean with lowest values in the eastern basin. In addition, total nitrogen (TN) concentrations and δ15N were analyzed on selected MSM72 stations using the persulfate-denitrifier method (Knapp et al., 2005).